A new species of Gamasiphis Berlese (Acari: Ologamasidae) from North Asia, with a key to the Eurasian species - Marchenko, Irina I. (Zootaxa, 2013)
Gamasiphis angaridis sp. n. is described from females and males collected from litter and soil in the North Asian part of Russia–Siberia and the Far East. This is the first species of the large genus Gamasiphis to be described from the northern Palaearctic Region. A key for the separation of females of the 11 recognisable species of Gamasiphis described inEurasia is provided.